The Influence of Intrinsic And Extrinsic Motivation On Student Learning Achievement With Learning Models (Offline, Online, And Hybrid) As Moderating Variable (Journal of Business and Management, 2022)
Motivation is components identified at the student internal factors that are linked to assure students' performance. Learning model as external factors affects students learning interest and the achievement of students’ understanding. However, during the pandemic, SBM ITB Undergraduate students experienced a decrease in learning motivation and the effectiveness of learning model (online, offline and hybrid) remains underexplored. Regardless of the level of motivation and the learning model implemented, students are still required to achieve optimal learning achievement. Therefore, to ensure student achievement remains optimal, this research is aimed to determine which learning model is the suitable to be applied in Undergraduate Program of SBM ITB. This research analyze the relationship between learning motivation (intrinsic and extrinsic) on student achievement and whether learning models moderate the relationship between motivation and learning achievement. This research also analyzes the effectiveness of three learning model based on student experiences and perception. The data were collected through a questionnaire, and a total of 155 students answered the questionnaire. Research hypotheses were tested using the multiple linear regression and moderated regression analysis. From the results, learning motivation (intrinsic and extrinsic) have positive relationship on learning achievement and learning model does not moderate the relationship between motivation and learning achievement. Based on the result analysis, the Undergraduate Program of SBM ITB does not need to be confused about the learning model to be chosen because there is no moderating effect given by the learning model. Based on learning model effectiveness comparison, students had a more favorable experience and perception of offline learning. Therefore, the researcher suggests that offline learning is the suitable learning model to be applicable in the Undergraduate Program of SBM ITB.Keywords: Intrinsic Motivation, Extrinsic Motivation, Learning Model, Learning Achievement